Identificación de zonas suceptibles a movimientos de masa en la vía Loja-Malacatos en el tramo comprendido entre Loja- Landangui. Provincia de Loja. - Tambo Encalada, Walter Simón (2009)
Given the different studies as both field cabinet has come to get different results that can be put into consideration as a basis for future studies that have the capital needed for the different processes involved. We used field methods such as direct observation to recognize the different characteristics in the study area and hence the development of the details of characterization of mass movements from the Universidad Nacional de Loja, as well as format for the inventory of mass movements in version 1.0, used by the Multinational Andean Project, Geoscience for Andean Communities (MAP-GAC), also saw the development of its distribution calicatas to hear and determine the local geology, so with a Trimble 5000 series topographic was carried out the survey of the various mass movements detected in the study area for which we are georeferenced using a GPS and taking in UTM coordinates X, Y and Z ; then be analyzed using software tools such as (9.2 ARGIS) and (AUTOCAD) 2008. It has been identified in the section of road Loja-Landangui there are slides which have a number ten, and it has come to identify the factors and triggers such as rainfall, loss of foot of slope and ground by the vibrations of passing vehicles. Within the cabinet studies, using tools such as GIS software (ARGIS 9.2) allowed to develop a number of maps that have been established according to the work performed in the study area and the requirements for obtaining a map susceptibility. Given the creation of the maps have some that are important as are the topographical and geological maps, but most stand out are the slope, lithology, vegetation and isohyet; themselves that are necessary to obtain a susceptibility map that is what they want to get as a final result in terms of maps are concerned. With regard to map areas of susceptibility was assessed very low, low, medium, high and very high susceptibility, where the area of areas with very low susceptibility is 329 Ha and includes the 2.4%, the low susceptibility area represents 6121 ha and covers 44.5%, half the area of 6888 Ha susceptibility is 50% and covers the area of high susceptibility is 418 Ha and covering 3.03% of the area and very high susceptibility according to the variables and weights used do not areas that are obtained within this classification. It was considered two slides for study in view of their area, where he has to slip DVL-L4 shows an area of 15.25 Ha and DVL-L7 has an area of 17.38 ha, which have been established measures of foresight as terracing, drainage and retaining walls which are detailed further in pursuing the study. Taking into account features in the study area has produced a map inventory and a map of susceptibility to mass movements and giving the actors the dissemination of this map and can make themselves known to the society for this given way to avoid building in these areas and therefore human and economic losses.